2012
DOI: 10.1093/cercor/bhs258
|View full text |Cite
|
Sign up to set email alerts
|

Neural Similarity Between Encoding and Retrieval is Related to Memory Via Hippocampal Interactions

Abstract: A fundamental principle in memory research is that memory is a function of the similarity between encoding and retrieval operations. Consistent with this principle, many neurobiological models of declarative memory assume that memory traces are stored in cortical regions, and the hippocampus facilitates the reactivation of these traces during retrieval. The present investigation tested the novel prediction that encoding-retrieval similarity can be observed and related to memory at the level of individual items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
277
5

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(318 citation statements)
references
References 44 publications
36
277
5
Order By: Relevance
“…Motivated by prior findings, we predicted that priming would be associated with reductions in neural activity across repetitions (repetition suppression; Maccotta and Buckner, 2004;Wig et al, 2005;Zago et al, 2005; Turk-Browne et al, 2006; Epstein et al, 2008), while successful recognition memory would be associated with consistency of representation across repetitions (pattern similarity; Xue et al, 2010;Ritchey et al, 2012). Critically, we sought to determine whether each of these relationships would be present within common, high-level visual cortical areas.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Motivated by prior findings, we predicted that priming would be associated with reductions in neural activity across repetitions (repetition suppression; Maccotta and Buckner, 2004;Wig et al, 2005;Zago et al, 2005; Turk-Browne et al, 2006; Epstein et al, 2008), while successful recognition memory would be associated with consistency of representation across repetitions (pattern similarity; Xue et al, 2010;Ritchey et al, 2012). Critically, we sought to determine whether each of these relationships would be present within common, high-level visual cortical areas.…”
Section: Introductionmentioning
confidence: 93%
“…Our finding that similarity across repetitions predicted subsequent recognition replicates the findings of Xue et al (2010), who observed relationships between pattern similarity and subsequent recognition of faces in similar neural regions (e.g., superior LOC). Explicit memory is also positively related to item-level pattern similarity in occipitotemporal regions when comparing encoding and recognition trials (i.e., when an encoded item is "repeated" in a recognition test) (Ritchey et al, 2012). Moreover, within ventral temporal cortex, similarity across different items within a category (e.g., similarity between two different scenes) is positively related to subsequent explicit memory (Kuhl et al, 2012a; LaRocque et al, 2013).…”
Section: Explicit Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…The increased spatial resolution afforded by such multivariate approaches enables investigation of event-specific cortical reinstatement. Two recent studies (Staresina et al 2012a;Ritchey et al 2013) were able to identify such item-specific reinstatement. Staresina et al (2012a) examined whether item-specific neural representations elicited during episodic encoding are later reinstated during successful recollection.…”
Section: Reinstatement Of Encoding Processes During Retrievalmentioning
confidence: 99%
“…MVPA, however, is unable to directly examine whether successful retrieval reinstates the neural representations of individual items. Representational similarity analysis supports neural reinstatement of individual stimuli (17)(18)(19), but this alternative fMRI approach does not examine to what extent retrieval reinstates a changing neural representation of context. In addition, the limited temporal resolution of fMRI studies makes them unable to identify the precise spatiotemporal dynamics of neural activity that distinguish successful and unsuccessful retrieval of individual events.…”
mentioning
confidence: 99%